Depth Perception with a Newly Developed Microscope Stereotest - Shinomiya K (Dove Medical Press, 2021)
Kayo Shinomiya,1 Takashi Fujikado,2 Akiko Kitora,1 Satoe Okamoto,1 Akiko Iwata,1 Yoko Ogushi,1 Yoshinori Mitamura1 1Department of Ophthalmology, Graduate School of Medicine, Tokushima University, Tokushima, Japan; 2Graduate School of Frontier Biosciences, Osaka University, Suita, Osaka, JapanCorrespondence: Kayo ShinomiyaDepartment of Ophthalmology, Graduate School of Medicine, Tokushima University, 3-18-15, Kuramoto-cho, Tokushima, 770-8503, JapanTel +81 088-633-7163Fax +81 088-631-4848Email shinomi@tokushima-u.ac.jpPurpose: We aimed to compare the depth perception under a microscope between binocular and monocular conditions using a newly developed microscopic stereotest (M-stereotest) and examine the effect of anisometropia on depth perception under a microscope.Subjects and Methods: Thirty young and healthy subjects were examined. A manipulator attached with a stainless wire was placed under the objective lens of a stereomicroscope. The wire was moved up manually, and the subjects were instructed to stop the knob movement once the wire reached the same height as the fixed two wires. The deviation from the height of the fixed wires was measured under a best optically corrected binocular, a best optically corrected monocular, or an anisometropic binocular [± 3 diopters (D) in the dominant or nondominant eye] condition.Results: The deviation was significantly smaller in the binocular condition than in the monocular dominant eye condition (0.38 ± 0.26 mm vs 1.89 ± 1.15 mm, p < 0.001) and was also significantly smaller in the best optically corrected binocular than in the anisometropic binocular condition [1.07 ± 1.00 mm (− 3.0 D), p = 0.003; 0.85 ± 0.67 mm (+3.0 D), p < 0.001].Conclusion: Depth perception under the microscope is more accurate under the binocular than in the monocular condition, indicating the potential role of stereopsis. Anisometropia deteriorates depth perception, suggesting that refractive error should be corrected during microscopic work, such as during ophthalmic surgery.Keywords: anisometropia, dynamic stereopsis, stereopsis, three-rods test